Africa's development impasse : rethinking the political economy of transformation - Andreasson, Stefan (Zed, 2010)
"Orthodox strategies for socio-economic development have failed spectacularly in southern Africa. Neither the developmental state nor neoliberal reform seems able to provide a solution to Africa's problems." "Africa's Development Impasse analyses this failure and explores the potential for alternatives. Examining why Botswana, Zimbabwe and South Africa have been unable to overcome a debilitating colonial legacy, the book argues that it is time to rethink the political economy of development. Building on the path-breaking work of post-development theorists, Stefan Andreasson navigates a new way through the current development impasse." "This important fusion of theory with empirical case studies is essential reading for students of development politics and Africa."--Jacket.